Squamous epitheliotropism of Enterovirus A71 in human epidermis and oral mucosa - Phyu, W.K.; Ong, Kien Chai; Kong, C.K.; Khalil, A.A.; Ramanujam, T.M.; Wong, Kum Thong (Nature Publishing Group, 2017)
Hand-foot-and-mouth disease is a self-limiting paediatric infectious disease commonly caused by Enterovirus A71 (Genus: Enterovirus, Family: Picornaviridae). Typical lesions in and around the hands, feet, oral cavity and other places may rarely be complicated by acute flaccid paralysis and acute encephalomyelitis. Although virus is readily cultured from skin vesicles and oral secretions, the cellular target/s of Enterovirus A71 in human skin and oral mucosa are unknown. In Enterovirus A71-infected human skin and oral mucosa organotypic cultures derived from the prepuce and lip biopsies, focal viral antigens and viral RNA were localized to cytoplasm of epidermal and mucosal squamous cells as early as 2 days post-infection. Viral antigens/RNA were associated with cytoplasmic vacuolation and cellular necrosis. Infected primary prepuce epidermal keratinocyte cultures showed cytopathic effects with concomitant detection of viral antigens from 2 days post-infection. Supernatant and/or tissue homogenates from prepuce skin organotypic cultures and primary prepuce keratinocyte cultures showed viral titres consistent with active viral replication. Our data strongly support Enterovirus A71 squamous epitheliotropism in the human epidermis and oral mucosa, and suggest that these organs are important primary and/or secondary viral replication sites that contribute significantly to oral and cutaneous viral shedding resulting in person-to-person transmission, and viraemia, which could lead to neuroinvasion.